Association between composite dietary antioxidant index and hyperlipidemia in adults based on the NHANES - Kaidi Nie; Tingting Deng; Yiling Bai; Yuxian Zhang; Zhixuan Chen; Xile Peng; Lina Xia; Jiao Liu (Scientific Reports)
Abstract Hyperlipidemia, a major risk factor for cardiovascular diseases, can potentially be alleviated by dietary antioxidants. This study explored the relationship between hyperlipidemia and the Composite Dietary Antioxidant Index (CDAI), which measures antioxidant intake from carotenoids, selenium, zinc, and vitamins A, C, and E. Analyzing data from 27,493 participants aged 20 and older from the National Health and Nutrition Examination Survey (NHANES) conducted between 2001 and 2018, we used weighted regression models to assess this association while adjusting for multiple covariates. Restricted cubic splines were also applied to check for any non-linear relationships. Findings revealed that higher CDAI scores significantly correlated with lower hyperlipidemia prevalence. Specifically, each unit increase in log-transformed CDAI was linked to a 14% decrease in hyperlipidemia risk (OR = 0.86, 95% CI: 0.77–0.95). Participants in the top CDAI quartile had a 15% lower hyperlipidemia prevalence compared to those in the bottom quartile (OR = 0.85, 95% CI: 0.77–0.95). No significant non-linear relationship was observed (p = 0.822). In conclusion, increased antioxidant intake, as measured by CDAI, is associated with reduced hyperlipidemia, underscoring the role of antioxidants in its management.